The Impact of Environmental Factors on Organizational Adoption of Human Resource Analytics in Sri Lankan Large-Scale Apparel Companies (Global Journal of Management and Business Research, 2020)
This study focuses on investigating the impact of environmental factors on organizational level of adoption to Human Resource Analytics in Sri Lankan apparel companies. Four variables were considered to develop the conceptual model under environmental factors impacting the adoption of Human Resource Analytics performed in prior studies. The sample consists with 210 Human Resource professionals which were taken based on nine out of thirteen key apparel companies in Sri Lanka. The findings revealed that the environmental factors and the organizational level of adoption have a positive relationship. The results indicated that the environmental factors lead to a strong positive impact on the organizational level of adoption.
Keywords: human resources analytics; organizational adoption; environmental factors